Ilaprazole for the treatment of gastro-esophageal reflux. (12th October 2016) - Savarino, Edoardo; Ottonello, Andrea; Martinucci, Irene; Dulbecco, Pietro; Savarino, Vincenzo
ABSTRACT: Introduction : Despite the undoubted benefit of proton pump inhibitors (PPIs), they have several shortcomings, such as a slow onset of action and a remarkable inter-individual variability, that limit the complete success of these drugs. Recently, a new PPI, ilaprazole, has been developed and used in GERD patients. Areas covered : The present review provides an update on the following points: current knowledge of GERD mechanisms; limitations of actual therapies; pharmacokinetic profile and metabolism of ilaprazole; initial studies on the therapeutic efficacy of ilaprazole in GERD. Expert opinion : Compared with all other approved PPIs, ilaprazole has shown an extended plasma half-life, a metabolism not significantly influenced by CYP2C19 genetic polymorphism and similar safety. This characteristics account for a low inter-individual variability, particularly in Asian populations, a higher suppression of gastric acid secretion, a more rapid acid control and consequent quicker symptom relief and a better effect on nocturnal acidity. However, clinical investigations assessing the efficacy of ilaprazole in the management of GERD are lacking and therefore the potential improvements achievable with ilaprazole in the current standard of care for acid-suppressing treatment must be confirmed in large and randomly controlled clinical trials enrolling patients with both erosive and non-erosive reflux disease.